Geschichte von unten: „Subaltern Studies” in Indien - Rothermund, Dietmar (Jahrbuch für Geschichte Lateinamerikas, 1998)
The „Subaltern Studies" intent to define a new approach to Indian history. They try to reveal the development of Indian society „from below" by challenging not only the British historiography on India but also the traditional Marxist interpretation of the Indian society and economy. These new studies are very much influenced by Gramsci and his term „subalternity", which does not concentrate mainly on economic or political domination, but on the cultural hegemony exercised by the ruling class.